Distribution of Dental Caries in Preschool Children Based on the dmf-T Index and Gender - Rusmiany, Putu; Rahina, Yudha; Nurdevianti, Ni Nyoman; Idaryati, Ni Putu (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Dental caries continues to be a major oral health problem among preschool children. The decayed, missing, and filled teeth (dmf-t) index is widely used as an indicator to assess caries status in this population. Gender has been suggested as a factor that may influence both the prevalence and severity of dental caries. Therefore, the objective of this study was to examine and compare the dmf-t index among preschool children according to gender. Material and Methods: This study employed a cross-sectional design with a purposively selected sample of 31 preschool children. Dental caries was assessed using the dmf-t index. Data were analyzed descriptively, and comparative analysis was conducted using the Mann-Whitney test. Results and Discussions: The results showed that the prevalence of dental caries among preschool children was 67.74%, with a mean caries score of 3.55 ± 4.06 falls within the moderate category. The prevalence of dental caries was higher in girls compared to boys (69.23% : 66.67%), whereas the mean caries score was higher in boys (4.39 ± 4.90 : 2.38 ± 2.14). Statistical analysis indicated no significant difference in the dmf-t index between boys and girls. Conclusion: Gender did not show a significant difference in caries experience. although the prevalence of dental caries was higher among girls, the mean caries experience was greater in boys.